Reactive nitrogen intermediates and outcome in severe adult malaria. - Taylor, A; Day, N; Sinh, D; Loc, P; Mai, T; Chau, T; Phu, N; Hien, T; White, N (1998)
The role of inducible nitric oxide synthase (iNOS) and nitric oxide (NO) in the pathophysiology of severe falciparum malaria remains unclear. We conducted a retrospective case-control study of Vietnamese adults with severe malaria to determine the relationship between outcome and admission plasma reactive nitrogen intermediates (RNI), the stable metabolites of NO. The study was designed to take into account the potential confounders of recent dietary nitrogen intake and renal function. Seventy-six patients who died from severe malaria were matched for age and sex with 76 survivors from a prospectively studied series of 560 patients. Median untransformed unadjusted plasma RNI levels were slightly higher in fatal cases (45 mumol/L, range 0-482) than in survivors (24.1 mumol/L, range 1.4-466) (P = 0.031, Wilcoxon signed-rank). There was a significant positive correlation between RNI levels and plasma creatinine (Spearman's rho = 0.35, P < 0.0001), and the addition of plasma creatinine as a covariate in a multivariate analysis abolished the trend towards higher RNI levels in fatal cases (P for the coefficient for RNI = 0.96). There was no association between RNI levels and either depth of coma on admission or time to regain consciousness. These findings do not support a pivotal role for systemic generation of NO in the pathogenesis of severe malaria in general, or cerebral malaria in particular.